Information Technology Risk Management Analysis Using Cobit and ISO at Jumputan Industry - Sutabri, Tata; Pratama, Yoga; Herdiansyah, M. Izman; Cholil, Widya (JOIV : International Journal on Informatics Visualization, 2025)
The Jumputan industry, a cultural heritage and creative sector in Palembang, utilizes data technology to streamline and improve business operations, thereby enhancing its competitiveness in transactions. This involves the use of computer devices and third-party applications accessible to the public. The integration of IT/IS in the Jumputan industry is often hindered by various challenges, such as connectivity issues, system malfunctions, outdated support, resource errors, insufficiently skilled personnel, shifts in technology policies by third-party providers, changes in government regulations, and other limiting factors. This study examined the risks associated with IT/IS implementation in the Jumputan industry, using the COBIT 2019 and ISO 31000 frameworks to identify risks, create risk profiles, and assess data technology management within the culture-based creative sector. This study aimed to identify and anticipate the risks associated with IT/IS implementation. A qualitative descriptive approach was employed, by data analyzed through the COBIT 2019 and ISO 31000 frameworks. The findings revealed that the Jumputan industry must adopt data technology risk management, as over 10 potential risk sources could negatively impact its business processes. Ultimately, this risk profile is intended to help the industry proactively address potential challenges and unforeseen risks. Additionally, it is hoped that this study will serve as a valuable resource for future research focused on the role of data technology in the creative industry.